Observations of stars occultations by the Moon with the "Spalakh" television system - Kleshchonok, V.V.; Buromsky, M.I. (Кинематика и физика небесных тел, 2005)
On the television observations of lunar occultations of the stars and reductions made in 2003–2004 at the Astronomical Observatory of the Kyiv National Taras Shevchenko University are reported. Observations are executed with the help of the “Spalakh” system with fixation Universal Time for each frame. On the exact moment of occultations is reported.